THE EXPLOITATION OF LOCAL LITHIC RESOURCES DURING THE LATE PREHISTORY OF NORTHWEST IBERIAN PENINSULA. (May 2015) - Rodríguez-Rellán, Carlos; Valcarce, Ramón Fábregas
<x content-type="archive" xml:space="preserve">Abstract</x> This paper explores the basic characteristics affecting the mechanical behavior of non-flint rocks, such as quartz and slate, during knapping. The impact of some of these features, such as anisotropy, cleavage, and the morphostructure on the selection and exploitation processes of quartz and slate is addressed through the analysis of the flaked assemblages of five Late Prehistory sites from NW Iberia. We suggest that the presence of characteristics providing a more homogeneous and controllable mechanical behavior would have had a significant role on the selection and exploitation of these raw materials. Also, certain traits a priori considered as non-suitable might be contemplated as rather advantageous for the knapping.